Aktualisasi Budaya Nyekar Dalam Membentuk Karakter Generasi Milenial Nahdiyah - doni saputra (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
The culture of a society will automatically shape the behavior of the community. We can see this in the Nyekar Ritual culture carried out by the Sidomulyo people. For some people, the Nyekar Ritual is simply a natural activity carried out to pray for someone who has died. For some Javanese people, nyekar especially to the graves of the embryo (danyang) of the village is nothing but a custom of respecting the spirits of their ancestors. In the view of Kejawen, respect for the ancestors is a value that is highly considered and must be a force that is deeply embedded in the Javanese personality. This is one of the characteristics of old Indonesian society, namely, a strong bond of social solidarity and blood ties. The actualization of the nyekar culture in Sidomulyo village is 1). The implementation of nyekar in Sidomulyo village is usually carried out in three places, namely: the Grave, the Village Opening Petilasan (rogo pati) and Sumber Jabalan. 2), Things that are done in Nyekar in Sidomulyo Village: send prayers / tahlil, sow flowers and burn incense / incense. 3), the result of the actualization of the nyekar culture is to shape the character of the nahdiyah millennial generation in the village of Sidomulyo into a religious generation. Gratitude for the Javanese people for all their gifts, harmony and tolerance or mutual respect.